Effects of a Natural Extract of Aronia melanocarpa Berry on Endothelial Cell Nitric Oxide Production. Issue 4 (2nd December 2015) - Varela, Claudia Elena; Fromentin, Emilie; Roller, Marc; Villarreal, Francisco; Ramirez‐Sanchez, Israel
Abstract: The effects of acute and chronic treatment with A ronia extracts on nitric oxide (NO) production and endothelial nitric oxide synthase (eNOS) phosphorylation in bovine coronary artery endothelial cells were investigated. Acute time course and concentration–response experiments were performed to determine the time and concentration at which A ronia induced maximal NO synthesis and eNOS phosphorylation. The findings indicate that relatively low concentrations (0.1 μg/mL) of Aronia extract significantly induced NO synthesis and eNOS phosphorylation after 10 min of treatment. Increased sensitivity of eNOS and a significant increase in NO synthesis resulted from longer term stimulation with Aronia (48 h) and an acute re‐treatment of the cells (10 min). Practical Applications: These in vitro results may be translated into potential future clinical applications where A ronia extracts may be used for prevention and coadjuvant treatment of cardiovascular diseases via increases in endothelial nitric oxide synthesis and related improvements in vascular functions. Given the dose–response effect of A ronia extract in vitro and metabolism of polyphenols that occurs in humans, dose–response studies would be necessary to define the optimal daily amount to be consumed.